Non‐Volatile Ferroelectric Memory with Position‐Addressable Polymer Semiconducting Nanowire. Issue 10 (18th March 2014) - Hwang, Sun Kak; Min, Sung‐Yong; Bae, Insung; Cho, Suk Man; Kim, Kang Lib; Lee, Tae‐Woo; Park, Cheolmin
<x xml:space="preserve">Abstract</x> One‐dimensional nanowires (NWs) have been extensively examined for numerous potential nano‐electronic device applications such as transistors, sensors, memories, and photodetectors. The ferroelectric‐gate field effect transistors (Fe‐FETs) with semiconducting NWs in particular in combination with ferroelectric polymers as gate insulating layers have attracted great attention because of their potential in high density memory integration. However, most of the devices still suffer from low yield of devices mainly due to the ill‐control of the location of NWs on a substrate. NWs randomly deposited on a substrate from solution‐dispersed droplet made it extremely difficult to fabricate arrays of NW Fe‐FETs. Moreover, rigid inorganic NWs were rarely applicable for flexible non‐volatile memories. Here, we present the NW Fe‐FETs with position‐addressable polymer semiconducting NWs. Polymer NWs precisely controlled in both location and number between source and drain electrode were achieved by direct electrohydrodynamic NW printing. The polymer NW Fe‐FETs with a ferroelectric poly(vinylidene fluoride‐co‐trifluoroethylene) exhibited non‐volatile ON/OFF current margin at zero gate voltage of approximately 102 with time‐dependent data retention and read/write endurance of more than 104 seconds and 102 cycles, respectively. Furthermore, our device showed characteristic bistable current hysteresis curves when being deformed with various bending radii and multiple bending cycles over 1000 times.